(untitled) (Agora for Physical Education and Sport, 2018)
The purpose of the present study was to explore the lived experiences of one male Paralympic athlete who maintained a longstanding relationship with his coach. This case provides insight into how a coach can serve as a key supportive agent in enabling an athlete to thrive both in sport and in life. The athlete was interviewed on two separate occasions and an interpretative phenomenological analysis was conducted. The athlete discussed the consequences of an acute bout of meningitis experienced at four years of age that left him impaired. During adolescence and adulthood, the athlete experienced the death of his mother and sister as well as the challenges associated with him assuming his homosexuality. Throughout these ordeals, his coach acted as a constant support figure. The athlete attributed much weight to his coach’s trust, respect, and empathy in explaining the significant success he attained on the international stage. The recommendations offered focus on how coaches can support athletes when athletes are navigating tough challenges.